An Act to Incorporate the Town of Dresden, Tennessee, and to Define Its Rights and Powers, ch. 202, § 3, pt. 16, 1901 Tenn. Pub. Acts 435, 437. - (:unkn) unknown (My University, 1901)
To regulate and suppress the shooting of guns and pistols and other firearms in the corporate limits."
Keywords: DISCHARGE